STERILIZATION IN SUNNAH CUPPING: INTEGRATING ISLAMIC ETHICS AND MODERN MEDICAL STANDARDS - Isdianto, Andik; Fitrianti, Novariza (PT. Jurnal Center Indonesia Publisher, 2025)
Sunnah cupping (hijamah) is a therapeutic practice rooted in Islamic tradition and widely acknowledged for its health benefits. However, improper sterilization of cupping instruments poses a significant risk of blood-borne infections such as hepatitis B, hepatitis C, and HIV. This study aims to explore the importance of equipment sterilization in sunnah cupping using a literature review approach. The method involves systematic thematic analysis of publications from 2010–2025 covering medical science, Islamic bioethics, and traditional health practices. Findings reveal that proper sterilization is crucial to preventing cross-contamination, and it aligns with Islamic ethical imperatives based on la darar wa la dirar and hifzh al-nafs. The discussion emphasizes the integration of Islamic values with modern medical standards and calls for structured education, practitioner training, and regulatory oversight. In conclusion, sterilization in sunnah cupping is not merely a technical requirement but a moral and religious obligation to ensure patient safety and uphold the integrity of prophetic medicine in the modern healthcare system.